2016
DOI: 10.1016/j.aprim.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Empatía médica en médicos que realizan el programa de formación médica especializada. Estudio comparativo intercultural en España

Abstract: Some factors involved in the development of empathy that are sensitive to cultural influence have been characterised. The development of future research areas is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
(23 reference statements)
0
7
1
17
Order By: Relevance
“…In physicians, punctuations observed for empathy and teamwork were slightly inferior than reported in previous studies with Latin American physicians-in-training (Delgado-Bolton et al, 2015; San Martín et al, 2016), but superior to those reported for lifelong learning (San Martín et al, 2016). Based on those differences, findings of this study are consistent with those reported in a previous cross-cultural study where the same specific elements of medical professionalism were compared between Spanish and Latin American physicians-in-training (San Martín et al, 2016).…”
Section: Discussioncontrasting
confidence: 85%
“…In physicians, punctuations observed for empathy and teamwork were slightly inferior than reported in previous studies with Latin American physicians-in-training (Delgado-Bolton et al, 2015; San Martín et al, 2016), but superior to those reported for lifelong learning (San Martín et al, 2016). Based on those differences, findings of this study are consistent with those reported in a previous cross-cultural study where the same specific elements of medical professionalism were compared between Spanish and Latin American physicians-in-training (San Martín et al, 2016).…”
Section: Discussioncontrasting
confidence: 85%
“…This explanation is not consistent with the studies that found that overall empathy did not decline, or with the results obtained in this study. 12,23,33 As a result, such suffering (which is real) is a necessary but insufficient condition to generate the empathic erosion process. However, this does not deny the fact that compassion may decline or become eroded because of the "personal adjustment" mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…24,[26][27][28][29][30] Empathy is not merely the mechanical connection of three components but the product of how the dialectical interaction occurs among these components, 10 and is the result of the evolutionary and ontogenetic development of subjects 31,32 who interact with environmental factors. 10,[33][34][35] As a consequence, dissecting the concept of empathy has a strictly analytical purpose. The CC component is associated with the emotional plane of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…24,[26][27][28][29][30] La empatía no es una unión mecánica de tres componentes, sino el producto de la forma en que se desarrolla la interacción dialéctica entre esos componentes 10 y es el resultado del desarrollo evolutivo y ontogenético del sujeto 31,32 en interacción con los factores ambientales. 10,[33][34][35] Como consecuencia, la disección del concepto de empatía tiene un objeto estrictamente analítico. El componente CC se asocia a la esfera emotiva o emocional del sujeto.…”
Section: Discussionunclassified
“…Tal explicación tampoco es consistente con aquellos estudios en los que la empatía general no declinó y tampoco lo es con los resultados obtenidos en este trabajo. 12,23,33 Como consecuencia, dicho sufrimiento (que es real) es una condición necesaria, pero no suficiente, para generar el proceso de erosión empática. Sin embargo, esto no niega el hecho de que la compasión pueda reducirse o erosionarse a causa del "ajuste personal" antes nombrado.…”
Section: Discussionunclassified